Case report: response to the ERK1/2 inhibitor ulixertinib in BRAF D594G cutaneous melanoma. Issue 4 (12th May 2022) - Wolfe, Zachary; Friedland, Julie C.; Ginn, Sarah; Blackham, Aaron; Demberger, Lauren; Horton, Morgan; McIntosh, Alyson; Sheikh, Hina; Box, Jessica; Knoerzer, Deborah; Federowicz, Bryan; Stuhlmiller, Timothy J.; et al.
Abstract : Melanoma is characterized by oncogenic mutations in pathways regulating cell growth, proliferation, and metabolism. Greater than 80% of primary melanoma cases harbor aberrant activation of the mitogen-activated protein kinase kinase/extracellular-signal-regulated kinase (MEK/ERK) pathway, with oncogenic mutations in BRAF, most notably BRAF V600E, being the most common. Significant progress has been made in BRAF-mutant melanoma using BRAF and MEK inhibitors; however, non-V600 BRAF mutations remain a challenge with limited treatment options. We report the case of an individual diagnosed with stage III BRAF D594G-mutant melanoma who experienced an extraordinary response to the ERK1/2 inhibitor ulixertinib as fourth-line therapy. Ulixertinib was obtained via an intermediate expanded access protocol with unique flexibility to permit both single-agent and combination treatments, dose adjustments, breaks in treatment to undergo surgery, and long-term preventive treatment following surgical resection offering this patient the potential for curative treatment.